2017
DOI: 10.1016/j.stem.2017.08.011
|View full text |Cite|
|
Sign up to set email alerts
|

Jak1 Integrates Cytokine Sensing to Regulate Hematopoietic Stem Cell Function and Stress Hematopoiesis

Abstract: SUMMARY JAK1 is a critical effector of pro-inflammatory cytokine signaling and plays important roles in immune function, while abnormal JAK1 activity has been linked to immunological and neoplastic diseases. Specific functions of JAK1 in the context of hematopoiesis, and specifically within hematopoietic stem cells (HSCs), have not clearly been delineated. Here, we show that conditional Jak1 loss in HSCs reduces their self-renewal and markedly alters lymphoid/myeloid differentiation in vivo. Jak1-deficient HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 46 publications
0
49
0
Order By: Relevance
“…Notably, this transcriptional program was significantly enriched in genes controlled by JAK1 in HSCs (ref. 18; Fig. 3I), supporting a potential convergent transcriptional mechanism between genetic inactivation of Phf6 and JAK-STAT signaling in HSC self-renewal.…”
Section: Phf6 Mutations Are Early Events In Leukemia Transformation Amentioning
confidence: 78%
See 1 more Smart Citation
“…Notably, this transcriptional program was significantly enriched in genes controlled by JAK1 in HSCs (ref. 18; Fig. 3I), supporting a potential convergent transcriptional mechanism between genetic inactivation of Phf6 and JAK-STAT signaling in HSC self-renewal.…”
Section: Phf6 Mutations Are Early Events In Leukemia Transformation Amentioning
confidence: 78%
“…We used the Jak1 mouse knockout hematopoietic stem cell signature gene set from ref. 18 31. For analysis of mouse tumors, human gene identifiers were converted to mouse in R using the biomaRt bioconductor package.…”
Section: Gene Set Enrichment Analysismentioning
confidence: 99%
“…Accordingly, somatic JAK1 GOF mutations are found in 10-20% of T-cell acute lymphoblastic leukemia (T-ALL) patients [35]. Recently, conditional JAK1 knock-out (KO) mice were developed, and RNA sequencing from isolated hematopoietic stem cells showed that the genes most affected by the loss of JAK1 were STAT1, STAT2, and multiple members of the IFN regulatory transcription family, confirming the important role of JAK1 in regulating these factors [36]. Moreover, it was shown that loss of JAK1 leads to decreased IFNγ sensitivity ex vivo.…”
Section: Discussionmentioning
confidence: 99%
“…This is reminiscent of the STAT-dependent transcriptional induction of pro-survival Bcl-2 family members in mouse cell lines (Catlett-Falcone et al, 1999;Fujio et al, 1997). Indeed, targeted disruption of JAK/STAT signaling in vivo in mice leads to reduced proliferation and decreased survival of multiple cell lineages, including the inner cell mass, and neuronal, hematopoietic and cardiac cells (Do et al, 2013;Kleppe et al, 2017;Levy and Lee, 2002;McLemore et al, 2001;Onishi and Zandstra, 2015;Takeda et al, 1997;Yoshida et al, 1996).…”
Section: Parallels In Jak/stat Signaling Across Tissues and Across Spmentioning
confidence: 94%